Effie olsen's summer special eaudiobook - Bilow, Rochelle (Books on Tape, 2024)
These childhood best friends swore they’d never speak again. But a surprise summer reunion changes everything when it gives them the chance to turn up the heat.   Effie Olsen thought she’d never live on the tiny Maine island where she grew up, but she’s returning from sixteen years as a professional chef in far-flung countries for one summer and one summer only. Her hometown boasts one of the best restaurants in the US, and lucky for her, Brown Butter needs a sous chef. Effie's eager for a chance at redemption after her last job went up in flames, but reluctant to set down roots in a place that reminds her of the ghosts of her past. Until, that is, she runs into Ernie Callahan, her onetime best friend who now works in the very same restaurant. Early morning swims and late-night games of truth or dare with Ernie remind her of what she’s been missing while traveling the world. He knows her better than anyone, and it doesn’t hurt that his smile lights her up brighter than the lighthouses dotting the craggy coastline. But their restaurant has a secret that’s bursting at the seams, and if Effie doesn’t keep it, her job will vanish into the foggy Maine air. As summer draws to a close, her dream job and the perfect guy are both within reach. Her salty seaside hometown might be the key to Effie’s sweet ending...if she can learn to let her heart lead the way in time.